Vukovar as example of multiethnic and divided city - Jagodar, Josip (Balcanica Posnaniensia. Acta et studia, 2018)
Vukovar is the city in the East Croatia on the border with the Republic of Serbia. In the paper I attempt to show the development of the city, the composition of its population and the relationships between ethnic groups from establishing of Vukovar until the beginning of the Homeland war in 1991. The paper presents the history of the Croat majority and the minorities which were, and which are, present in the city: the Germans, Hungarians, Serbs, Rusyns, Ukrainians, Yews and the Slovaks. From the beginning Vukovar was a multicultural, multiethnic and multiconfessional city thanks to migrations which were present since its establishing, in which the Croats were the majority. After the WWI a large number of Serbs immigrated into this area. The political situation gave them benefits which earlier belonged to Germans and Hungarians. They gained power to rule the city. It became the source of constant tensions between the Serbian and Croatian population in the period of Yugoslavia (1918-1941) and during the WWII (1941-1944). Although the communist Yugoslav authorities were trying to pacify interethnic differences, the escalation of nationalisms brought about the siege and the capture of Vukovar in 1991 by the Serbian troops.